2018
DOI: 10.1038/s41598-018-25310-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miRNAs in cervical mucus as a novel diagnostic marker for cervical neoplasia

Abstract: microRNAs (miRNAs) play important roles in regulation of gene expression during cervical carcinogenesis. We investigated expression profiles of miRNAs in cervical cancer and its precursor lesions by utilizing cervical mucus. Cervical mucus was collected from 230 patients with a normal cervix, cervical intraepithelial neoplasia (CIN), squamous cell carcinoma (SCC), or adenocarcinoma (AD). The levels of miRNA in the mucus were quantified by miRNA array and real-time reverse-transcriptase polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 35 publications
(36 reference statements)
2
48
0
Order By: Relevance
“…Accordingly, we hypothesized that miR-126-3p promotes carcinogenesis. However, we observed that levels of miR-126-3p in patients with cervical cancer fluctuate (22). We also found variability in the amounts of miR-126-3p in cervical cancer cells themselves (Fig.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Accordingly, we hypothesized that miR-126-3p promotes carcinogenesis. However, we observed that levels of miR-126-3p in patients with cervical cancer fluctuate (22). We also found variability in the amounts of miR-126-3p in cervical cancer cells themselves (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…We previously found that miR-126-3p is highly expressed in patients with overt cervical cancer or precursor lesions compared with normal cells (22). Accordingly, we hypothesized that miR-126-3p promotes carcinogenesis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our results are in accordance with many other studies (Tanaka et al, 2009;Elhamamsy et al, 2017) who reported that mir-92a plasma levels were significantly lower in AML patients and also it was found to be very low in tumor tissues retrieved from patients with gastric cancer (Zhao et al, 2018), However, other studies found that suppression of miR-92a will induce apoptosis and can be considered as a novel method for treatment of Acute Promyelocytic Leukemia (Sharifi et al, 2014). Also, upregulation in miR-92a was observed in colorectal cancer (Elshafei et al, 2017) and cervical cancer (Zhou et al, 2015;Kawai et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…[6,[8][9][10] Several new biomarkers have been applied for detection of transformed cells aiming to increase the sensitivity and/or specificity of the screening tests and/or in combination with cytology and/or with HPV DNA testing [8,11]. More recently, several groups have demonstrated aberrant expression of microRNAs (miRNAs) in premalignant and malignant cervical lesions, suggesting that this might be used as a more specific biomarker [3,[12][13][14][15][16][17][18][19]. The majority of these works analyzed cervical cancer and/or premalignant lesions, with no surrounding tumor-free tissues coming from the same patient.…”
Section: Introductionmentioning
confidence: 99%